Dynamic Transcriptomic and Metabolomic Analyses of Madhuca pasquieri (Dubard) H. J. Lam During the Post-germination Stages - Kan, Lei; Liao, Qicong; Chen, Zhipeng; Wang, Shuyu; Ma, Yifei; Su, Zhiyao; Zhang, Lu (Frontiers in Plant Science, 2021)
The wild population of Madhuca pasquieri (Dubard) H. J. Lam is currently dwindling; its understory seedlings are rare, and there is a lack of molecular studies, which impedes the conservation of this species. This study exploited second-generation sequencing and widely targeted metabolomics analysis to uncover the dynamic changes in differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs) in five post-germination stages of M. pasquieri whole organism. Notably, the weighted gene co-expression network analysis (WGCNA), transcriptome, and metabolome association analyses all indicated significant enrichment of the flavonoid biosynthesis pathway in stage 4 (two-leaf), and an upregulation of the genes encoding flavonol biosynthesis in this stage. In stage 5 (nine-leaf), the flavonols were significantly accumulated, indicating that the changes in metabolites were driven at the transcript level. According to the significant changes in gene expression encoding auxin transport carriers and their correlation with flavonols during stage 5, the flavonols were speculated to have a direct inhibitory effect on the expression of PIN4 encoding gene, which may inhibit the process of polar auxin transport. The results provided important insights into the molecular network relationships between the transcription and metabolism of this rare and endangered species during the post-germination stages and explained the reasons for the slow growth of its seedlings at the molecular level.